1975
DOI: 10.1159/000271506
|View full text |Cite
|
Sign up to set email alerts
|

Are There Sex Differences in Creativity across the Adult Life Span?

Abstract: The purpose of this study was to examine sex differences of young, middle-aged, and older adults in creative problem solving and preference for complexity of visual figures and to explore the part degree of sex role identification might play in this relationship. 111 teachers, aged 20–83 years, took a battery of seven creativity tests, two intelligence measures, and the masculinity-femininity scale of the MMPI. Sex differences were found on only one creativity test (p < 0.01); this test taps figural abilities.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1
2

Year Published

1978
1978
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 2 publications
0
2
1
2
Order By: Relevance
“…Our general finding of equivalence in originality for younger and older adults differs from previous cognitive studies of creativity, which typically found agerelated declines in creativity (Alpaugh & Birren, 1977;Alpaugh, Parham, Cole, & Birren, 1982;Guilford, 1967;Jaquish & Ripple, 1981;McCrae, Arenberg, & Costa, 1987;Ruth & Birren, 1985; for a review, see Denney, 1990). We believe that the differences stem from two sources.…”
Section: Discussioncontrasting
confidence: 98%
“…Our general finding of equivalence in originality for younger and older adults differs from previous cognitive studies of creativity, which typically found agerelated declines in creativity (Alpaugh & Birren, 1977;Alpaugh, Parham, Cole, & Birren, 1982;Guilford, 1967;Jaquish & Ripple, 1981;McCrae, Arenberg, & Costa, 1987;Ruth & Birren, 1985; for a review, see Denney, 1990). We believe that the differences stem from two sources.…”
Section: Discussioncontrasting
confidence: 98%
“…Evidence for sex differences in creativity is, however, more allusive, but that may be a methodological artifact. Research on sex differences in creativity often operationalizes creativity in terms of mental flexibility, fluency, and originality (Ai, 1999; Alpaugh & Birren, 1975; Baer & Kaufman, 2008; Kogan, 1974; Matud, Rodríguez, & Grande, 2007). In contrast, measures of creative achievement (something closer to what we have measured in this study) appear to reveal some sex differences (Abra & Valentine-French, 1991).…”
Section: Individual Differences In Creativitymentioning
confidence: 99%
“…Originality and creativity are all too rare, and I know of no evidence that these traits are more frequent in one sex [13]. As we busily compare candidates, adding up their papers and calculating impact factors, do we remember to look for these qualities?…”
Section: Job Searches In Academiamentioning
confidence: 99%